Double partitioning of the left atrium: a previously unreported echocardiographic finding in a case in which transoesophageal echocardiography aided operative resection. Issue 3 (September 1991) - Bu'Lock, F A; Murphy, P; Martin, R P
Abstract : Precordial echocardiography showed two membranes obstructing pulmonary venous return in the left atrium of a 9 month old infant. This anomaly has not previously been described; therefore transoesophageal echocardiography was performed at the time of surgery. This confirmed the anatomy and aided complete resection of both membranes. Even in small infants transoesophageal echocardiography can provide useful information about complex atrial malformations.